Advancements in sustainable material development: A Comprehensive review of coir fiber and its composites - Imran, Al Ichlas; Siregar, Januar Parlaungan; Cionita, Tezara; Hadi, Agung Efriyo; Setiyo, Muji; Mat Rejab, Mohd. Ruzaimi; Jaafar, Jamiluddin; Fitriyana, Deni Fajar; Dewi, Rozanna (Universitas Muhammadiyah Magelang, 2024)
Derived from Coir coconut waste, coir fiber offers an environmentally friendly response to ecological challenges in various industries. Its application aligns with achieving Sustainable Development Goals (SDGs), such as eliminating extreme poverty, ensuring food security, and promoting decent employment and economic expansion. It also fosters environmentally friendly consumption and production, mitigates global warming, and conserves biodiversity. The study involves a comprehensive review of current literature, examining the methodologies including extraction techniques, surface modifications, and manufacturing processes like hand layup, casting, compression molding, hot pressing, and injection molding. The analysis identifies key improvements in mechanical, thermal, and physical properties of coir fiber composites, particularly enhanced tensile strength, thermal stability, and reduced water absorption due to chemical treatments. This confirms previous findings and contributes toward enhancing our understanding that coir fiber is extensively utilized in multiple industries, including housing, construction, transportation, biomedical, wrapping, electrical power, communication technology, biofuel, and bioenergy due to their natural abundance, affordability, ease of shaping, superior durability, and eco-friendly characteristics. Another crucial practical implication is that coir fiber and its composites offer numerous advantages that have significant consequences for the development of coir fiber in various fields.